Self-assembly of stabilized droplets from liquid-liquid phase separation for higher-order structures and functions - Naz, Mehwish (Macmillan Publishers Ltd part of Springer Nature, 2025)
Dynamic microscale droplets produced by liquid-liquid phase separation (LLPS) have emerged as appealing biomaterials due to their remarkable features. However, the instability of droplets limits the construction of population-level structures with collective behaviors. Here we first provide a brief background of droplets in the context of materials properties. Subsequently, we discuss current strategies for stabilizing droplets including physical separation and chemical modulation. We also discuss the recent development of LLPS droplets for various applications such as synthetic cells and biomedical materials. Finally, we give insights on how stabilized droplets can self-assemble into higher-order structures displaying coordinated functions to fully exploit their potentials in bottom-up synthetic biology and biomedical applications.